Respostas

A melhor resposta!
2014-08-07T11:14:45-03:00
O vértice de uma parábola é dado por
y_{v} = \frac{delta}{4a}   , sendo delta = b²-4ac
x_{v} = -\frac{-b}{2a}

a) 
y_{v} = -\frac{ (-6)^{2}-4*1*8}{4*1}
y_{v} = -\frac{ 36-32}{4}
y_{v} = -1

x_{v} = \frac{-(-6)}{2*1}
x_{v} = 3

b) 
y_{v} = -\frac{ 4^{2}-4*(-2)*0}{4*(-2)}
y_{v} = -\frac{ 16-0}{-8}
y_{v} = 2

x_{v} = \frac{-4}{2*(-2)}
x_{v} = 1

c) 
y_{v} = -\frac{ (-4)^{2}-4*1*4}{4*1}
y_{v} = -\frac{ 16-16}{4}
y_{v} = 0

x_{v} = \frac{-(-4)}{2*1}
x_{v} = -2
4 4 4